2019
DOI: 10.1186/s12893-019-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent papillary thyroid carcinoma diagnosed in surgically treated patients for primary versus secondary hyperparathyroidism: same incidence, different characteristics

Abstract: Background The coexistence of hyperparathyroidism and thyroid cancer presents important diagnostic and management challenges. With minimally invasive parathyroid surgery trending, preoperative thyroid imaging becomes more important as concomitant thyroid and parathyroid lesions are reported. The aim of the study was to evaluate the rate of thyroid cancer in patients operated for either primary (PHPT) or secondary hyperparathyroidism (SHPT). Methods Our retrospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
6
11
1
Order By: Relevance
“…In previous literature, the prevalence of concomitant PTC in pPHT ranged from 2% to 15%, consistent with our results. Preda et al [18] recently reported the incidence of thyroid cancer in patients with sHPT to be 11.7%, which was higher than our findings of 7.2%. Our study demonstrated that the incidence of PTC was high and similar in both patients with pHPT and sHPT.…”
Section: Discussioncontrasting
confidence: 92%
“…In previous literature, the prevalence of concomitant PTC in pPHT ranged from 2% to 15%, consistent with our results. Preda et al [18] recently reported the incidence of thyroid cancer in patients with sHPT to be 11.7%, which was higher than our findings of 7.2%. Our study demonstrated that the incidence of PTC was high and similar in both patients with pHPT and sHPT.…”
Section: Discussioncontrasting
confidence: 92%
“…Despite the high incidence of PTC in PHPT patients, the association between sporadic PHPT and PTC is still controversial. Previous studies demonstrated that most of the PTC foci in PHPT patients were papillary microcarcinoma (PMC), which was consistent with our finding [ 15 , 20 ]. When compared with patients of PTC alone, the concomitant PTC in PHPT patients showed significantly smaller tumor diameters, leading some researchers to believe that the PTC was overdiagnosed in PHPT patients [ 7 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…PTC is the most common type of the malignant thyroid lesions synchronous with PHPT [ 13 15 ]. Ogburn and Black were the first to report the concomitant PTC in PHPT patients in 1956 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with Ψ the complex conjugated of Ψ, is implicit and unmanifest, while in the presence of the growth factor it becomes explicit and manifest. For other details, see [22][23][24]; v)we prove that on a fractal medium, the implicit-explicit transition of information implies the fractal type spontaneous breaking symmetry (for general details, see [25][26][27]). Then, a specific calibration becomes functional, calibration which enables a holographic implementation of the interaction entity-fractal medium (for example celltissue).…”
Section: Mathematical Modelmentioning
confidence: 99%